Gestão socioambiental estratégica: uma proposta para PMEs - Ribeiro, Daniela Pereira (2008)
In the last two decades, the social problems are mobilizing business to direct actions to Implement strategies management, in order to survive and fortify themselves on their competitive arena. The development of social and ecological conscience in global society has also involve the business sector in search a socially responsible attitude. Thus, organizations are modeling their strategies to deal more this demand that the environment determines. This study was applied in a collective transport company of Santa Maria/RS and has as objective to develop a management model strategic socio-environmental for small and medium business (SMB), with relation to corporate socio-environmental responsibility, integrating the social, environmental and economic aspects. To reach these objectives were established the following specific objectives: (1) analyze the models of strategic management and socioenvironmental management existing; (2) confront the precepts inherent to corporate socio-environmental responsibility, strategic management and socio-environmental management. (3) identify the main organizational factors that may influence to change the SMB toward as placing socio-environmental responsible. This research is a social research, as nature is qualitative, regarding the technique is exploratory, in a participatory planning, in particular the methodology of research-action. The proposed model of strategic socio-environmental management for SMB is a tool which has the goal of helping the SMB to deploy a process of managing allied to corporative social responsibility, in the adoption of sustainable practices in a simple and efficient way. The research allowed the identification of some advantages and benefits for the SMB, such as the visualization of the real situation of the undertaking in relation to its sustainability, the promotion of education for the employees, the integration of socio-environmental variables in strategic planning, the development of technological options with accessible cost to the strategic socio-environmental management, the dissemination of culture of strategic socio-environmental planning for SMB and the possibility of precise monitoring of operational, tactic and strategic indicators, adopting, in that way, reliable procedures for the continuous improvement.